(untitled) - Mikusova, Miroslava; David, Andrej (Doprava a spoje, 2010)
The paper presents different approaches applicable in public transport quality evaluations, such as European Foundation for Quality Management (EFQM) model, certification, Total Quality Management (TQM), ISO quality standards, The Malcolm Baldrige National Quality Award (MBQA) approach, etc. It also describes the benchmarking - the systematic approach that provides to performance assessment and identification of best practice - as a powerful tool for the development of performance, quality sustainability and economic efficiency of transport enterprises.